Rainbow graft for tip reconstruction in revision rhinoplasty. Issue 3 (March 2020) - Bracaglia, Roberto; Servillo, Maria; Fortunato, Regina; Pino, Valentina; Albanese, Roberta; Gentileschi, Stefano
Summary: Patients undergoing revision rhinoplasty can show complex tip deformities such as asymmetry, dome angulation with cartilage interruption, alar pinch and retraction, and underprojection. When these defects are present at the same time, often multiple cartilage grafts are needed to restore a pleasing tip and functional external nasal valve. This study reports our experience with the rainbow graft, a previously described technique that can repair with a single cartilage graft the above-mentioned defects. We performed a retrospective review of 21 patients who had undergone revision rhinoplasty between 2006 and 2017 employing the rainbow graft technique to correct complex tip deformities. The presence of tip deformities such as asymmetry, dome angulation with cartilage interruption, alar pinch, alar retraction, and under/overprojection was recorded preoperatively and postoperatively. Complete photographic documentation was done, and Rhinoplasty Outcome Evaluation (ROE) questionnaire was administered to the patients. Five patients were male and 16 were females. Mean age of patients was 40 ± 7.6 years. Follow-up ranged from 1 to 12 years, mean 5 ± 3 years. Eight patients had undergone one rhinoplasty, 10 patients had undergone two, and three patients had undergone three. Before surgery, all patients showed asymmetry, 20 dome angulation, 19 alar pinch, and 18 retraction. Eight showed tip overprojection, six underprojection, and seven no alteration of tip projection. The mean ROE score was 20.23 ± 7.37. After surgery, two patients showed persistent asymmetry, none had dome angulation, one alar pinch, and two alar retraction. Projection was corrected in every patient. We observed no case of graft infection, malposition, or resorption, and corrections achieved remained stable during follow-up. Mean postoperative ROE score was 80.75 ± 6.24. Its improvement was statistically significant ( p  < 0.001). The rainbow graft is a safe and effective technique in revision rhinoplasty indicated for the total restoration of nasal tip appearance in the presence of complex secondary deformities.